The influence of Exchange Rate and Freight Cost Toward Export Volume of Adidas at PT Apparel One Indonesia 1 Semarang - Adelia Regita Putri; Endang - Sulistiyani; Paniya - Paniya (JOBS (Jurnal Of Business Studies), 2020)
Exports volume of Adidas from time to time is not stable because the amount always fluctuates and shows the decrease every year. This study aims to determine the effect of the exchange rate and freight cost partially and simultaneously on the export volume of Adidas at PT Apparel One Indonesia 1 and to find out how much all independent variables contribute to the dependent variable. The independent variables used in this study are the exchange rate and freight cost, while the dependent variable is the export volume of Adidas. This research uses an explanatory research type with a quantitative approach. The data used in this study is secondary data from literature reviews and observations, and comes from PT Apparel One Indonesia 1 with a time series from January 2014 to December 2019 and Bank Indonesia from January 2014 to December 2019. The output of this study shows that both variables affect export volume simultaneously. Meanwhile, partially, the exchange rate variable has a negative and significant effect on the export volume of Adidas. The freight cost variable has a negative and significant effect on the export volume of Adidas